Geoffrey of Monmouth and Breton aristocracy in 12th century England: Social and political contexts of “On the deeds of the Britons” - S. G. Mereminskiy (Шаги, 2023)
The article is devoted to reconstructing the social context of the works of Geoffrey of Monmouth, one of the most prominent 12th-century English historical writers. For this, a corpus of documents is analyzed, in which Geoffrey himself and his probable patrons appear, as well as the textual history of the historian’s writings, primarily the “On the deeds of the Britons”. This analysis make it possible to put forward a number of conclusions. Geoffrey himself most likely belonged to a family of Breton immigrants to England, although there is no direct evidence of this. Geoffrey’s patron in the 1130s and the 1140s, Walter, Archdeacon of Oxford, was part of the entourage of the Anglo-Breton baron Brian Fitz-Count, court knight of King Henry I, and later one of the leading supporters of his daughter, Empress Matilda. It is most likely that it was through Brian that Walter and Geoffrey got in touch with Robert, Earl of Gloucester, Empress Matilda’s brother and dedicatee of the original version of the “On the deeds of the Britons”. Perhaps it was through Brian and his wife Matilda that a copy of Geoffrey’s book came to the Norman Abbey of Bec, where it was found in January 1139 by another English historian, Henry of Huntingdon. Around 1141, possibly due to the failures of the ‘Angevin’ party and Brian personally, Archdeacon Walter began to establish contacts with King Stephen’s supporters, including with representatives of the Beaumont family, one of whom, Count Waleran, became the dedicatee of a slightly revised version of the ‘On the deeds of the Britons’.